Comparative Analysis of Lower Limb Muscle Activity During Isometric External Rotation in Static and Dynamic Modeling Approaches - Miłosz Chrzan; Robert Michnik; Sławomir Suchoń; Michał Burkacki; Katarzyna Nowakowska-Lipiec (Applied Sciences)
This study investigates differences in lower limb muscle activity during isometric external hip rotation while standing using static and dynamic models within the AnyBody Modeling System. Thirty-three participants performed controlled isometric rotations using a custom-designed device capable of simultaneously measuring rotational moments and ground reaction forces. Both static and dynamic simulations were conducted for each subject using personalized biomechanical models. Muscle activity values at the point of peak rotational moment were analyzed for twelve key muscles involved in hip rotation and stabilization of the knee joint, and statistical differences were assessed for significance. Muscles from the gluteal group (Gluteus minimus, medius, and maximus) generally showed lower activation in dynamic simulations, although this trend was not statistically significant for all muscles or test conditions. The mean difference in muscle activity values between static and dynamic simulations was between 0.03 and 0.08 for the gluteal group muscles and up to 0.15 for the Iliopsoas. Static models overestimated the role of stabilizers. Significant differences (p ≤ 0.05, Wilcoxon signed-rank test) were observed between the two approaches in terms of predicted muscle activation. In conclusion, discrepancies in muscle activity predictions between static and dynamic simulations highlight the need for task-specific simulation design and careful result interpretation.